Development of switchable planar reflectors for beam shaping realization - Abbasi, Muhammad Inam (2016)
This work provides an extensive analysis for the design and performance optimization of planar reflectors within X-band and Ku-band frequency ranges. The objective of this work was to investigate the feasibility of using strategic slot embedded patch element configurations for an efficient reconfigurable reflectarray antenna design. PIN diodes were incorporated with single and multiple slot embedded patch element configurations for the design of beam switchable planar reflectors. Moreover unit cells based on liquid crystal substrates were also designed for comparison between two reconfigurable planar reflector design techniques. 3Dimensional electromagnetic computer models of CST Microwave Studio and Ansoft HFSS were used for the simulations and the results of unit cells were practically verified by waveguide scattering parameter measurements using vector network analyzer. Performance characterization for bandwidth and reflection loss optimization of different slot embedded patch configurations was done based on the scattering parameter measurements. Maximum frequency variation of 2.56GHz with dynamic phase range of 346 ̊ in X-band was demonstrated by rectangular slots in the centre and circular slots along width configuration while Ku-band measured results demonstrated a maximum frequency variation of 2.54GHz with dynamic phase range of 278 ̊ for circular slot with gap configuration. The measured scattering parameter results for the PIN diodes based elements designed in X-band frequency range are shown to provide a maximum frequency tunability of 0.55GHz with 238 ̊ of dynamic phase range in the case of embedded rectangular slots in the centre of patch element. On the other hand liquid crystal based embedded rectangular slots unit cells designed in X-band frequency range are shown to demonstrate comparatively lesser frequency tunability of 0.12GHz with dynamic phase range of 103 ̊. Although liquid crystal based design is shown to offer good frequency tunability and dynamic phase range, however the loss associated with liquid crystals is one of the limitations of this design. Higher tunable loss factor of 1.91dB was demonstrated by liquid crystal based design as compared to tunable loss factor of 1.43dB shown by PIN diode based design. The investigations were further extended by carrying out equivalent circuit analysis of PIN diode based and liquid crystal based designs for detailed characterization of reconfigurable planar reflector designs. Equivalent circuit model is demonstrated to offer a very close agreement between the simulated and scattering parameter measured results where a maximum discrepancy of 0.1dB was observed. A comprehensive mathematical model based on Finite Element Method (FEM) was proposed for progressive phase distribution to develop a novel design technique to create a reconfigurable reflectarray antenna based on strategic slot configurations. The developed model permits the positioning of an individual element of the array, required for progressive phase distribution, independent of its geometrical structure. Furthermore the developed algorithm can be used for both centre fed and off-set fed planar reflector designs while incorporating the effect of material properties of conductor and substrate. Three novel robust periodic reflectarray configurations, consisting of 144, 64 and 36 elements respectively were designed and fabricated for far-field radiation pattern measurements. The measured radiation patterns are shown to offer close agreement with the predicted results where switchable array based on PIN diodes confirmed a beam switching of +6 ̊,0 ̊and -6 ̊ while the passive 144, 64 and 36 elements arrays are observed to give maximum 3dB beamwidth of 10.5 ̊, 11.4 ̊ and 13.2 ̊ respectively.